2024
DOI: 10.1021/acsapm.3c03006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distance Effect of Negative Ion–Porous Organic Polymers on the Electrochemical Properties of Composite Solid Electrolytes

Haibin Wang,
Jun Liu,
Wenting Tai
et al.

Abstract: Among composite solid electrolytes, the addition of fillers could restrain the crystallization of the molecular chain of poly(ethylene oxide) (PEO). However, the impact of the spatial distance on the electrochemical properties remains unstudied. This paper uses linear aldehydes with carbon chain lengths of 1 and 7 to synthesize polyaminal-formaldehyde (PAN-FDE) and polyaminal-heptaldehyde (PAN-HDE) with melamine as the filler, which can reduce the crystallinity of the matrix and improve the ionic conductivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…It can be found that after 50 cycles, the RCTS of NHCS/S and NHCS/Mn 3 O 4 /S cathodes decrease to 30.8 Ω and 16.2 Ω, Rs are 26.2 Ω and 11.5 Ω, and R e are 1.6 Ω and 1.5 Ω, respectively. The decrease of Rct resistance indicates that the conductive layer effectively inhibits the shuttle of LiPSs and accelerates the interfacial charge transfer 28 , 29 . The resistance values of NHCS/Mn 3 O 4 /S cathode before and after cycling are smaller than NHCS/S, indicating that it has higher conductivity, which is consistent with Raman results.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that after 50 cycles, the RCTS of NHCS/S and NHCS/Mn 3 O 4 /S cathodes decrease to 30.8 Ω and 16.2 Ω, Rs are 26.2 Ω and 11.5 Ω, and R e are 1.6 Ω and 1.5 Ω, respectively. The decrease of Rct resistance indicates that the conductive layer effectively inhibits the shuttle of LiPSs and accelerates the interfacial charge transfer 28 , 29 . The resistance values of NHCS/Mn 3 O 4 /S cathode before and after cycling are smaller than NHCS/S, indicating that it has higher conductivity, which is consistent with Raman results.…”
Section: Resultsmentioning
confidence: 99%